Living and Dying with a Disability in Debtor Society Why Context Matters in Assisted Suicide Debates - Brock, Brian 1970- (2018)
Economic rationalities are a central component of the malignant social positioning of people with all sorts of disability and mental health issues today. The author traces the role of economic rationality in positioning some lives today as not really worth living. This widespread willingness of the general populace in Western liberal democracies to map their political relations in economic terms is historically novel in the West, and is one of the more noteworthy marks the transition points into, and out of, Christendom. The author examines the impact of the rise of the cultural settlement called Christendom for social outsiders, suggesting that they provide illuminating contrasts with some of the characteristic practices and moral assumptions of our contemporary Western liberal democracies. The conclusion of the article is that a society without a working account of mercy and forgiveness will find it difficult conceptually to explicate practices associated with valuing human lives that are considered noncontributors within accounts of political life grounded in economic rationalities.
Keywords: Christian Theology; value of life; Disability; Eugenics; Euthanasia